Individual risk preference as a predictor of health behaviour: evidence from the use of condoms against HIV/AIDS in Ghana - Abel Gbogbolu; Edward Nketiah-Amponsah (BMC, 2023)
Abstract Background It is evident that public health education interventions to promote the use of condoms against HIV infections in Ghana have yielded modest results. However, existing studies in the field of sexual and reproductive health in Ghana have failed to account for differences in risk preferences of individuals. This study fills the gap by investigating how individuals' risk preferences predict their behaviour toward using condoms against HIV in Ghana. Method Conceptually, the study followed the Grossman health capital theoretical model for risk preference and health behaviour nexus. Data were obtained from the most recent Ghana Living Standards Survey Round 7 (GLSS 7), conducted in 2017. Using data from GLSS 7, a probit regression model was estimated to show how the risk preferences of individuals that did not abstain from sex predicted their use of condoms against HIV. To ensure robustness, two scenarios of declared risk preferences were used to predict the use of condom behaviour against HIV. Results Probit regression estimation shows that the risk preferences of individuals that did not abstain from sex significantly predicted their use of condoms against HIV in Ghana. Even though the study found that the predicted probability of using a condom reduces among risk-averse individuals that do not abstain from sex, not using a condom against HIV was found to be worse among risk lovers. Conclusion The study provides empirical evidence that public health education against HIV/AIDS in Ghana cannot continue to ignore the risk preference of individuals. The results of this study have immediate implications, first for a comprehensive and continuous measurement of risk preferences among Ghanaians in major household surveys going forward. At the moment, the latest round of the GLSS is just about the only household survey in Ghana that has attempted to collect some data on individual time and risk preferences using only hypothetical monetary rewards. Second is the immediate consideration of individual risk preferences in public health education campaigns against HIV/AIDS in Ghana.